PREDICTION OF COOPERATIVE TAX AVOIDANCE AND FINANCIAL STRATEGY - Sugiyanto, Sugiyanto; Dewi, Lely Savitri (Rescollacom (Research Collaborations Community), 2023)
One of the problems faced by cooperative managers is related to tax compliance, on the other hand, it is related to the ability to increase cooperative surplus that can be used for reinvestment, dividends, and other social funds. Conflicts of interest are faced by management as agents of cooperative members and also tax authorities. This study aims to predict tax avoidance by using operating efficiency, capital intensity and leverage variables as the basis for formulating tax planning strategies that can be carried out by cooperative managers. The research uses descriptive quantitative and regression analysis to predict the independent variables that determine tax avoidance. The results showed that only two independent variables were significant to predict tax avoidance, namely operating efficiency, and leverage. While capital intensity is not significant. The strategy that must be set by cooperative managers by utilizing the two significant variables to conduct tax planning through tax avoidance.